2011 5th International Conference on Bioinformatics and Biomedical Engineering 2011
DOI: 10.1109/icbbe.2011.5780854
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Groundwater Renewability in Beijing Plain Area

Abstract: Groundwater is the main water source of Beijing plain area. It plays a vital role in the safety of water supply. Assessment of the groundwater renewability in study area is important to its water resources sustainable utilization. In this study, 5 thematic maps including precipitation, precipitation infiltration coefficient, aquifer structure, slope and, drainage density were selected to integrate using ArcGIS software. Standardization of index values is expressed by membership function. The weights were assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Rapid urbanization is enlarging the gap between metropolitan areas and suburban areas. Zheng et al [7] have confirmed that the groundwater renewability varied across the Beijing Plain. Therefore, the spatial variation of groundwater level is a necessity in Beijing Plain as well as other urban areas globally.…”
Section: Introductionmentioning
confidence: 91%
“…Rapid urbanization is enlarging the gap between metropolitan areas and suburban areas. Zheng et al [7] have confirmed that the groundwater renewability varied across the Beijing Plain. Therefore, the spatial variation of groundwater level is a necessity in Beijing Plain as well as other urban areas globally.…”
Section: Introductionmentioning
confidence: 91%
“…The renewability of groundwater systems depends largely on the quantity and quality of aquifer recharge [48]. Turnover time (a) is an indicator of groundwater renewal capacity [49]. It refers to the ratio between the total storage of groundwater in aquifer (m 3 ) and the amount of groundwater system recharge per unit time (m 3 /a).…”
Section: Effect Of Residence Time On Fe and Mnmentioning
confidence: 99%